A Review of Machine Learning Botnet Detection Techniques based on Network Traffic Log - Ibrahim Z.-A.; Razali R.A.; Ismail S.A.; Azhar I.H.K.; Rahim F.A.; Azilan A.M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Crime; Cybersecurity; Denial-of-service attack; HIgh speed networks; Internet of things; Machine learning; Network security; Personal computing; Botmaster; Botnet detections; Botnets; Cyber-attacks; High-speed Networks; Introduction; Log.; Machine-learning; Network traffic; Related works; Botnet